ATMOSPHERIC PARAMETERS AND CHEMICAL COMPOSITION OF PECULIAR STARS HR465, HD91375, and HD25354 - Yushchenko, V.; Gopka, V.; Yushchenko, A.; Shavrina, A.; Hubrig, S.; Musaev, F. (Одеські астрономічні публікації, 2008)
We present the results of determinations of the atmospheric parameters and chemical composition of three chemically peculiar stars: HR465, HD91375, and HD25354. We used the observations made at 1.8 meter Bohuynsan observatory (Korea), 1.88 meter Haute-Provence observatory (France), 2.0 meter Terskol observatory (Russia), and 8.2 meter ESO telescopes. The effective temperatures of HR465 and HD25354 are higher than the values, found in earlier investigations. The detailed abundance pattern of HD91375 is found for the first time, the star is a typical member of Am or Ap group.